Analiza przyczyn stresu zawodowego w opinii pielęgniarek = An analysis of the causes of occupational stress in the opinions of nurses - Pietraszek, Agata; Charzyńska-Gula, Marianna; Łuczyk, Marta; Szadowska-Szlachetka, Zdzisława; Kachaniuk, Hanna; Kwiatkowska, Joanna (Journal of Education, Health and Sport, 2016)
Pietraszek Agata, Charzyńska-Gula Marianna, Łuczyk Marta, Szadowska‑Szlachetka Zdzisława, Kachaniuk Hanna, Kwiatkowska Joanna. Analiza przyczyn stresu zawodowego w opinii pielęgniarek = An analysis of the causes of occupational stress in the opinions of nurses. Journal of Education, Health and Sport. 2016;6(9):643-652. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.158951 http://ojs.ukw.edu.pl/index.php/johs/article/view/3862 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 24.09.2016. Analiza przyczyn stresu zawodowego w opinii pielęgniarek An analysis of the causes of occupational stress in the opinions of nurses Agata Pietraszek1, Marianna Charzyńska-Gula2, Marta Łuczyk1, Zdzisława Szadowska‑Szlachetka1, Hanna Kachaniuk3, Joanna Kwiatkowska4 Zakład Onkologii, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie Wydział Nauk Społecznych i Humanistycznych, Państwowa Wyższa Szkoła im. prof. Stanisława Tarnowskiego w Tarnobrzegu Zakład Medycyny Rodzinnej i Pielęgniarstwa Środowiskowego, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie Zakład Etyki i Filozofii Człowieka, Katedra Nauk Humanistycznych, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie Adres korespondencyjny: Agata Pietraszek, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie, ul. S. Staszica 4/6, 20-059 Lublin, e mail: agata.pietraszek.umlub@gmail.com Streszczenie Wstęp. Stres zawodowy występuje wtedy, kiedy pracownicy doświadczają dyskomfortu psychicznego związanego z warunkami bądź wymaganiami pracy, w sytuacji, gdy przekraczają one ich możliwości. Cel badań. Celem badani było poznanie opinii pielęgniarek na temat czynników stresogennych występujących w miejscu pracy. Materiał i metody. Badaniami objęto grupę 278 osób wykonujących zawód pielęgniarki. W badaniach zastosowano metodę sondażu diagnostycznego z techniką ankiety, z zastosowaniem autorskiego kwestionariusza ankiety. Otrzymane dane poddano analizie statystycznej w oparciu o oprogramowanie komputerowe Statistica 10.0. Wyniki i wnioski. Większość badanych pielęgniarek była usatysfakcjonowana z pracy zawodowej (85%). Nawet 95,6% badanych twierdziło, że zawód pielęgniarki jest stresujący. Dodatkowo 56,1% badanych twierdziło, że jest codziennie narażona na stres zawodowy. Znaczny odsetek respondentów deklarowało radzenie sobie ze stresem w pracy. Czynniki, które wywołują znaczący poziom stresu wśród większości pielęgniarek to niska pensja (43,53%), a także nagłe pogorszenie stanu zdrowia pacjenta i konieczność reanimacji (39,93%). Zmienne, które istotnie różnicują opinie badanego personelu pielęgniarskiego to: wiek, stan cywilny, miejsce zamieszkania, liczba potomstwa, pełnione stanowisko oraz kontakt ze śmiercią i umieraniem pacjentów w codziennej praktyce zawodowej. Słowa kluczowe: stres psychologiczny; pielęgniarki; narażenie zawodowe Abstract Introduction. Occupational stress occurs when workers experience mental discomfort due to working conditions or requirements which exceed their capabilities. Objective. The objective of the study was to identify the opinions of nurses on stress factors at their workplace. Material and methods. The survey covered a group of 278 individuals performing the profession of a nurse. The diagnostic survey method was applied together with a self-designed questionnaire. The obtained data was subjected to statistical analysis with the use of the Statistica 10.0 software. Results and conclusions. Most of the surveyed nurses were satisfied with their professional work (85%). As many as 95.6% of them claimed that their profession is stressful. Furthermore, 56.1% of the respondents admitted that they were exposed to occupational stress on a daily basis. A considerable percentage of the surveyed declared being able to deal with stress at work. The factors that contribute to a substantial level of stress of most nurses include low remuneration (43.53%), and a sudden decline in a patient’s condition and the necessity of resuscitation (39.93%). The variables that constitute significant differentiating factors of the opinions of the nursing personnel are: age, marital status, place of residence, number of children, job position and contact with death and dying patients in the daily nursing practice. Key words: stress, psychological; nurses; occupational exposure